Analysis of Factors Affecting Firm Value in Property, Real Estate and Building Construction Companies Listed on the Indonesia Stock Exchange for the 2014-2018 Period - Marselia Purnama; Vivin Hanitha; Adrian Hidayat (Fakultas Bisnis, 2021)
This research was conducted at companies engaged in the property, real estate & building construction sector which are listed on the Indonesia Stock Exchange.In this study using purposive sample method as a sampling method. The number of samples used was 6 companies with research data conducted from 2014 to 2018 so that 30 observational data were obtained. In testing the hypothesis in this study carried out in six ways, namely the regression model test, classical assumption test, multiple linear regression analysis, partial test (t test), simultaneous test (f test), and test the coefficient of determination.From the results of this study it can be concluded that simultaneously all variables have a significant effect on firm value. The results of the regression analysis show an adjusted value of 0.486599, which means that the variation of Current Ratio, Debt to Equity Ratio, Net Profit Margi, Return on Equity and Earning per Share can explain 48.66% of the variation in firm value. While the remaining 51.34% is explained by other variables not examined in this study.